Baker’s Theory of Material Constitution and Thinking Things into Existence - Kıymaz, Tufan (Filozofia Nauki, 2018)
The paper provides a critical evaluation of Lynne Rudder Baker’s nonmereological theory of material constitution in light of the “thinking into existence” objection, formulated by Theodore Sider and Dean W. Zimmerman. Although Baker responds to it, she focuses on its specific versions presented by Sider and Zimmerman and does not address the source of the problem. Baker maintains that beliefs, social practices, and conventions can bring a new intention-dependent object into existence. However, as I argue, the thinking into existence objection shows that constituted objects, if there are any, are ontologically independent of beliefs, social practices, and conventions. In fact, Baker’s theory doesn’t give us any reason for believing that intention-dependent objects are any more real than fictional objects.